Pengaruh Senam Lansia terhadap Penurunan Tekanan Darah dan Kadar Kolesterol Darah pada Lansia di Masa Pandemi Covid-19 - Risnawati Risnawati; Erni Eka Sari (STIKes Surya Global Yogyakarta, 2022)
Background of the study: In 2018 the elderly population in Indonesia reached 24.49 million people (9.27%). There are many various diseases can attack to elderly such as diabetes, stroke, hypertension, coronary heart complications caused by high cholesterol. It can be called degenerative disease. By doing elderly gymnastics regularly, it can regulate blood pressure and blood cholesterol levels within normal limits so it can make free from various disease.Methods: Pre-experimental quantitative research type with one group pretest-posttest design. The number of samples in this study were 35 elderly people who actively participated in gymnastics using the purposive sampling technique. Data analysis with univariate analysis, bivariate using Wilcoxon Sign Rank Test. Results: Statistical analysis showed was the influence of gymnastics elderly with a reduction in blood pressure of the sistolic (p = 0.000), there was the influence of gymnastics elderly with a decrease in diastolic blood pressure (p = 0.000), and there was the influence of gymnastics elderly to decrease blood cholesterol levels (p = 0.000). Conclusion: there was the influence of gymnastics elderly to decrease blood pressure and blood cholesterol levels in elderly during a pandemic covid-19 in Posyandu Bilante village Larompong district of Luwu. Keywords: Elderly, Elderly Gymnastics, Blood Pressure, Blood Cholesterol Levels